Microbial profiles associated improving bioelectricity generation from sludge fermentation liquid via microbial fuel cells with adding fruit waste extracts. (October 2021) - He, Junguo; Xin, Xiaodong; Pei, Zheng; Chen, Lingyu; Chu, Zhaorui; Zhao, Meihua; Wu, Xuewei; Li, Biqing; Tang, Xia; Xiao, Xiannian
Highlights: Fruit waste extracts raised microbial diversity with more power generation via MFCs. Cooperation of key members and interactions toward bioelectrogenesis were proposed. An illustration of co-locating scenario for maximizing power recovery was evaluated. Abstract: This first-attempt study illustrated the microbial cooperative interactions related to bioelectricity generation from the mixture of sludge fermentation liquid (SFL) and fruit waste extracts (FWEs) via microbial fuel cells (MFCs). The optimal output voltages of 0.65 V for SFL-MFCs, 0.51 V for FWEs-MFCs and 0.75 V for mixture-MFCs associated with bioelectricity conversion efficiencies of 1.061, 0.718 and 1.391 kWh/kg COD were reached, respectively. FWEs addition for substrates C/N ratio optimization contributed considerably to increase SFL-fed MFCs performance via triggering a higher microbial diversity, larger relatively abundance of functional genes and microbial synergistic interactions with genera enrichment of Clostridium, Alicycliphilus, Thermomonas, Geobacter, Paludibaculum, Pseudomonas, Taibaiella and Comamonas . Furthermore, a conceptual illustration of co-locating scenario of wastewater treatment plant(s), waste sludge in situ acidogenic fermentation, fruit waste collection/crushing station and MFC plant was proposed for the first time, which provided new thinking for future waste sludge treatment toward maximizing solid reduction and power recovery.